Salt Specificity of a Reduced Nicotinamide Adenine Dinucleotide Oxidase Prepared from a Halophilic Bacterium - Hochstein, L. I. (1968)
Extracts prepared from a halophilic bacterium contained a reduced nicotinamide adenine dinucleotide (NADH(2)) oxidase active at high solute concentrations. The cation requirement was nonspecific, since KCl, RbCl, and CsCl replaced NaCl with little or no loss of activity, and NH(4)Cl was only partially effective. Only LiCl failed to replace NaCl. No specific chloride requirement was observed although not all anions replaced chloride. Bromide, nitrate, and iodide were essentially ineffective, whereas acetate, formate, citrate, and sulfate proved suitable. The presence of sulfate affected the ability of a cation to satisfy the solute requirement. Sulfate enhanced the rate of NADH(2) oxidation when compared with the rate observed in the presence of chloride. Cations which were inactive as chlorides (LiCl and MgCl(2) at high concentrations) satisfied the cation requirement when added as sulfate salts. Although magnesium satisfied the cation requirement, a concentration effect, as well as an anion effect, was observed. In the presence of MgCl(2), little NADH(2) oxidation was observed at concentrations greater than 1 m. At lower concentrations, the rate of oxidation increased, reaching a maximal value at 0.1 m and remaining constant up to a concentration of 0.05 m MgCl(2). Magnesium acetate and MgSO(4) also replaced NaCl, and the maximal rate of oxidation occurred at 0.05 m with respect to magnesium. There was no change in the rate of oxidation at high magnesium acetate concentrations, whereas the rate of NADH(2) oxidation increased at higher concentrations of MgSO(4).